2021
DOI: 10.1038/s41598-021-00249-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity and mode of action of 1,8-cineol against carbapenemase-producing Klebsiella pneumoniae

Abstract: Antimicrobial resistance remains one of the most challenging issues that threatens the health of people around the world. Plant-derived natural compounds have received considerable attention for their potential role to mitigate antibiotic resistance. This study was carried out to assess the antimicrobial activity and mode of action of a monoterpene, 1,8-cineol (CN) against carbapenemase-producing Klebsiella pneumoniae (KPC-KP). Results showed that resazurin microplate assay and time-kill analysis revealed bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
1
26
1
1
Order By: Relevance
“…Moreover, 1,8-cineole had strong effect against Bacillus cereus and Cryptococcus neoformans at a dose of 2 mg/mL [ 32 ]. A trial conducted by Moo et al [ 33 ], illustrated that 1,8-cineol has potent activity against carbapenemase-producing Klebsiella pneumoniae (KPC-KP) at 28.83 mg/mL. In this study, the authors demonstrated that 1,8-cineol induced oxidative stress and membrane damage, resulting in KPC-KP cell death.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Moreover, 1,8-cineole had strong effect against Bacillus cereus and Cryptococcus neoformans at a dose of 2 mg/mL [ 32 ]. A trial conducted by Moo et al [ 33 ], illustrated that 1,8-cineol has potent activity against carbapenemase-producing Klebsiella pneumoniae (KPC-KP) at 28.83 mg/mL. In this study, the authors demonstrated that 1,8-cineol induced oxidative stress and membrane damage, resulting in KPC-KP cell death.…”
Section: Discussionmentioning
confidence: 60%
“…In this study, the authors demonstrated that 1,8-cineol induced oxidative stress and membrane damage, resulting in KPC-KP cell death. This was observed by scanning and transmission electron microscopies, which confirmed bacterial cell membrane rupture and loss of intracellular materials [ 33 ]. It is well known that there are limits to the use of essential oils and their main compounds because of their toxicity.…”
Section: Discussionmentioning
confidence: 85%
“…In addition, the encapsulation of 1,8-cineole in nanofibers can prolong fungal activities against Candida species given that the isolated compound is not a strong fungal agent [ 52 , 53 , 54 ]. 1,8-Cineole also has potential as an antimicrobial, repellent, and anticancer agent and can be used in the treatment of respiratory diseases, including COVID-19 [ 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…To obtain cineol in a sufficient yield for antimicrobial testing, it was isolated from eucalyptus oil (TechnicoFlor, Allauch, France) by using the method which depends on the fact that cineole combines with acids as phosphoric acid to form loose compounds that are easily decomposed when treated with water (Mukherjee 2019 ). The isolated cineole (yield 80% w/w) was dehydrated over anhydrous sodium sulphate and subjected to NMR analysis to confirm its purity before using for antimicrobial study.…”
Section: Methodsmentioning
confidence: 99%